Hábito lector y expresión oral formal en sujetos vascoparlantes que tienen el castellano como segunda lengua - Otxagabia Letamendia, Garazi (Huarte de San Juan. Filología y Didáctica de la Lengua, 2014)
This article is a summary of a homonym study presented as master final project. The main aim of this research is to analyse the influence of the reading habit in the formal oral expression of second language learners. Our hypothesis believes that if learners are not exposed to contexts where the formal oral expression is worked, there will be no essential differences between both learners with or without the reading habit. For that purpose, a sample of 12 bilingual (Basque-Spanish) participants, aged 14, was taken among students of the third course at the high school level in the centre Andra Mari Ikastola from Etxarri-Aranatz. According to the tests conducted, the results show that, even though the learners with the reading habit obtained better marks in some linguistic aspects, it cannot be stated that the practice of reading itself has influenced the level of the oral expression. Other factors, such as the oral practice of the speakers, the knowledge of the language within the family or the individual effort of each student prove to be relevant in the explanation of the results.